1997
DOI: 10.1046/j.1365-2923.1997.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Problem‐based medical education: development of a theoretical foundation and a science‐based professional attitude

Abstract: Problem-based learning, combined with early patient contact, integration between different subject areas, elements of multiprofessional education, and special emphasis on the development of communications skills has become the basis for the medical curriculum at the Faculty of Health Sciences in Linköping. Critics have questioned the depth of the scientific and theoretical aspects of the curriculum. Through a series of specific measures in the organization of the curriculum and examinations, and due to the ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…A student-driven ward at the Health University of Linkoping and a Clinical Skills Laboratory at Faculty of Medicine in Copenhagen was the inspiration in this choice of methods (Dahle et al, 1997;Aspegren, 1999).…”
Section: The Organisationmentioning
confidence: 99%
“…A student-driven ward at the Health University of Linkoping and a Clinical Skills Laboratory at Faculty of Medicine in Copenhagen was the inspiration in this choice of methods (Dahle et al, 1997;Aspegren, 1999).…”
Section: The Organisationmentioning
confidence: 99%
“…The use of the MEQ has also been reported by other PBL medical schools. 14,24,25,32,46,61,[67][68][69][70] Clinical reasoning test modules. 71 Clinical reasoning test modules were developed at Southern Illinois University from the PBL Module 72 to reflect the hypothetico-deductive model of reasoning.…”
Section: Outcome-oriented Instrumentsmentioning
confidence: 99%
“…Furthermore, including mandatory scientific works and readings was thought to allow for the development of a science-based professional attitude. 69 No study of reliability and validity was reported. Tutor, peer, and self-assessment.…”
Section: Process-oriented Instrumentsmentioning
confidence: 99%
“…EPC is appreciated by students (Friedberg & Glick 1997;Johnson & Scott 1998;Vieira et al 2003) and valued by staff (Friedberg & Glick 1997;Johnson & Scott 1998). Comparing outcomes in performance has been problematic due to small sample sizes (Pamies et al 1994) and the difficulties of longitudinal follow up (Dahle et al 1997). A recent systematic review concluded that it 'helps medical students learn, helps them develop appropriate attitudes towards their studies and future practice, and orientates medical curricula towards society's needs' (Littlewood et al 2005).…”
Section: Introductionmentioning
confidence: 99%